2018
DOI: 10.1186/s13058-018-1018-7
|View full text |Cite
|
Sign up to set email alerts
|

Tricho-rhino-phalangeal syndrome 1 protein functions as a scaffold required for ubiquitin-specific protease 4-directed histone deacetylase 2 de-ubiquitination and tumor growth

Abstract: BackgroundAlthough numerous studies have reported that tricho-rhino-phalangeal syndrome type I (TRPS1) protein, the only reported atypical GATA transcription factor, is overexpressed in various carcinomas, the underlying mechanism(s) by which it contributes to cancer remain unknown.MethodsBoth overexpression and knockdown of TRPS1 assays were performed to examine the effect of TRPS1 on histone deacetylase 2 (HDAC2) protein level and luminal breast cancer cell proliferation. Also, RT-qRCR, luciferase reporter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Activity of the NuRD complex is involved in gene regulation of numerous processes including pluripotency during embryonic development or transcriptional events involved in cancer formation or progression (Basta and Rauchman 2015). TRPS1 stabilizes HDAC2 expression, and reduced cell viability caused by low TRPS1 levels can be rescued by HDAC2 overexpression (Wang et al 2018b), even though we did not observe any changes in HDAC1 or HDAC2 expression upon TRPS1 loss. In addition, we now show that DNA binding of the core enzymatic components of the NuRD complex (HDAC1 and HDAC2) is reduced upon TRPS1 loss.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Activity of the NuRD complex is involved in gene regulation of numerous processes including pluripotency during embryonic development or transcriptional events involved in cancer formation or progression (Basta and Rauchman 2015). TRPS1 stabilizes HDAC2 expression, and reduced cell viability caused by low TRPS1 levels can be rescued by HDAC2 overexpression (Wang et al 2018b), even though we did not observe any changes in HDAC1 or HDAC2 expression upon TRPS1 loss. In addition, we now show that DNA binding of the core enzymatic components of the NuRD complex (HDAC1 and HDAC2) is reduced upon TRPS1 loss.…”
Section: Discussionmentioning
confidence: 55%
“…TRPS1 is also shown to be essential and required for growth of (mostly hormone receptor-positive) breast cancers (Witwicki et al 2018). Indeed, several breast cancer cell lines show reduced growth both in vitro and in vivo upon loss of TRPS1 expression (Elster et al 2018;Wang et al 2018b;Witwicki et al 2018). In other settings, loss of TRPS1 expression appears to be promoting mammary tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, we recently reported that TRPS1 promoted tumor growth by functioning as a scaffold to regulate USP4-directed HDAC2 deubiquitination. These observations provided a mechanistic insight into the tumor growth-promoting role of TRPS1 (35).…”
Section: Trps1 Suppresses Tumor Initiation By Repressing Sox2 Expressmentioning
confidence: 85%
“…Another study indicated that USP4 promotes breast cancer cell invasion through the Relaxin/TGF‐β1/Smad2/MMP‐9 axis . Furthermore, a TRPS1–USP4–HDAC2 axis that contributes to tumor growth was established …”
Section: Discussionmentioning
confidence: 99%